Detecção de Pasteurella multocida em pulmões de suínos abatidos no estado de Mato Grosso através da qPCR - Chitarra, Cristiane Silva (2013)
Porcine Respiratory Disease Complex (PRDC) is an importante respiratory diseases in pigs, causing economic losses in the swine production. Pasteurella multocida (P. multocida) is considered one of the most important pathogens of swine respiratory system, causing progressive atrophic rhinitis, when associated with Bordetella bronchiseptica, septicemia and pneumonia in pigs. However, little is known about the pathogenesis of pneumonia by that agent. The aim of this study is to quantify P. multocida in lungs of slaughtered pigs with and without pneumonia by qPCR technique and evaluate the interactions between bacteria and viruses by analyzing the association and the correlation between them using qPCR, microbiological and histopathological examinations of the lungs. Samples were collected between the period of 2010 and 2011, in total 109 samples of lungs in two slaughter house under Federal Inspection in the State of Mato Grosso. Of the 109 samples collected, 61 samples showed no macroscopic lesions (control group) and 48 samples with macroscopic lesions of pulmonary consolidation, deposition of fibrin on the pleura, pleurisy and / or adhesion. A total of 45.8% (22/48) of lung lesion group and 4.9% (3/61) of the group without lesions were positive for P. multocida isolation, being the only significant association with the lesion and control groups (p <0.000). The occurrence of more than one microorganism was observed with and without lung injury. Based on the number of copies of the kmt1 gene of P. multocida present in the lesion group (8.25 copies) and in the control group (1.6 copies) there is a significant difference (p <0.05). The qPCR technique for detection of P. multocida was efficient for being more sensitive than the microbiological method, demonstrating that a larger number of kmt1 gene copies is in GL suggest that P. multocida is an important agent in the development of pneumonia.